Evaluation of Antimicrobial Potentialities of Leaves Extract of the Plant Cassia tora Linn. (Leguminosae/Caesalpinioideae) - Bhattacharya, Monisankar Samanta, Soma Ghosh, Suman Datta; Amalesh Samanta*, Gouranga Das, Durbadal Ojha, Bolay (Journal of Phytology, 2010)
SUMMARY Cassia tora L. (Family Leguminosae/Caesalpinioideae), is a plant with enormous medicinal values. The chloroform, methanol and aqueous extract of leaves of Cassia tora L. showed antibacterial activity (0-5000 Î¼g/ml) against 38, 58 and 29 bacterial strains respectively out of 120 various bacterial strains and also methanol extracts showed antifungal activity (0-64mg/ml) against 3 strains out of 4 strains. Five strains of Shigella dysenteriae, four strains of Staphylococcus aureus, and three strains of Escherichia coli, have shown sensitivity against in vitro treatment of the methanol extracts up to 2000 Î¼g/ml concentration. The minimum inhibitory concentration (MIC) values ranges from 2â€“64 mg/ml for dermatophytes. Minimal Bactericidal Concentration (MBC) value lies in the range of 2000-2500 Î¼g/ml against Escherichia coli ATCC25938 and Shigella dysenteriae 1. Phytochemical study indicates that the leaf extract contains flavonoids, saponins, resins, phytosterol, alkaloids and carbohydrates. The traditional claim of leaves of C. tora as an antimicrobial property have been confirmed as the extracts displayed activity against some bacteria and fungi which cause skin infection and gastro-intestinal disorder. Key words: Cassia tora plant, Phytochemical study, Antimicrobial activity, MIC and MBC <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Gouranga Das et al. Evaluation of Antimicrobial Potentialities of Leaves Extract of the Plant Cassia tora Linn. (Leguminosae/Caesalpinioideae). J Phytol 2/5 (2010) Â 64-72.